Economic Valuation of Hypothetical Paratransit Retrofitting - Naili Huda; Kim Peter Hassall; Sunarto - Kaleg; Abdul - Hapid (National Research and Innovation Agency, 2015)
This paper describes a feasibility analysis of conventional and retrofitted paratransits, comparing economic performance of conventional paratransit with those using lead acid and lithium batteries. Research object is Dago-Kalapa paratransit in Bandung, West Java, travelling the distance of 11 km in town, under 8 peak hour operation. After calculating the estimated annual cost and benefit; net present value (NPV), payback period (PBP) and internal rate of return (IRR) then were quantified to provide feasibility description of those three paratransits. In addition, a sensitivity analysis regarding discount rate, gasoline price and battery price is given to offer broader sense of factors embraced. It is found that both gasoline and lead acid paratransit have big NPVs with only slight differences, while lithium paratransit has negative NPV. This phenomenon applies to their PBPs and IRRs as well. Only when gasoline costs reaches IDR 15,000 will electric paratransit prevails over conventional one. Thus, it can be inferred that at the moment, paratransit runs with gasoline is still the most cost effective compared to its counterparts. However, starting retrofitting from now is endorsed due to its environmental benefit.